Laparoskopska vstavitev ventrikuloperitonealne drenaže zaradi normotenzivnega hidrocefalusa. Prikaz primera in nove operacijske tehnike - Velnar, Tomaž (Zdravniški vestnik, 2012)
Ventriculoperitoneal drainage is a widely accepted technique for the management of normal press ure hydrocephalus. With the advent of minimally invasive techniques, laparoscopy is being increasingly used for shunt placement. We present a patient treated for normal pressure hydrocephalus with laparoscopically guided ventriculoperitoneal drainage placement. A short review of the disease and surgical technique is discussed.
Keywords: hidrocefalus; intracranial pressure; laparoscopy; laparoskopija; normal pressure hydrocephalus; therapy; ventriculoperitioneal drainage; ventrikuloperitonealna drenaža; zdravljenje; znotrajlobanjski tlak